Well-differentiated mesenteric liposarcoma: report of two cases. - Poillucci, Gaetano; Podda, Mauro; Pisanu, Adolfo; Gomes, Carlos Augusto; Gallo, Gaetano; Di Saverio, Salomone; De Angelis, Renato (Acta Biomedica Atenei Parmensis, 2022)
Liposarcoma is a rare tumor that can be treated by surgery in the absence of distant metastases. Management of liposarcoma, including diagnosis and therapy, is challenging because it has no characteristic symptoms and no established effective treatment. Here, we report two rare cases of primary mesenteric liposarcoma. In the first case, the tumor caused small bowel obstruction, and the patient presented with abdominal distention and severe abdominal pain. The second case is an occasional finding that occurred during laparoscopic surgery for incisional hernia. Both patients underwent successful resection of the tumor. Histopathology found a well-differentiated liposarcoma in both cases.